Optimalisasi Sistem Pengangkutan Sampah Di Kabupaten Bengkayang Berbasis Geographic Information System (GIS) - Putra, Ezzwar Dwi; Utomo, Kiki Prio; Sulastri, Aini (Jurnal Teknologi Lingkungan Lahan Basah, 2023)
The solid waste transportation system in Bengkayang Regency is currently not effective. This is due to unfinished facilities and infrastructure also low level of public awareness about not being disciplined in disposing of waste on time, polluted the environment. This study aims to find out the pattern of the existing waste transportation system in Bengkayang Regency and provide solutions for optimizing the waste transportation system with the help of GIS applications. The research methodology used is direct measurement in the field or on existing conditions, which refers to the Minister of Public Works Regulation No. 3 of 2013. The results of measuring waste transport cycles under existing conditions amount to 1 trip per day and several routes that have not been effective with two transportation systems, namely the HCS   and SCS, where waste transportation routes and routes can be optimized by making the shortest route at the longest route distance from TPS to TPA Magmagan, which is 30.92 km. GIS is used to get an alternative route of transportation with the greatest distance, namely a garbage truck with police number KB 8257 KF to the final processing site by taking a shorter route than the existing route, which 28.14 km, therefore it"™s necessary to add a route alternative.